Investigations into the operational effectiveness of hybrid laminar flow control aircraft - Young, T. M. (Cranfield University, 2002)
Hybrid Laminar Flow Control (HLFC) is an active drag reduction technique that permits extended laminar flow on an aircraft surface at chord Reynolds numbers normally associated with turbulent flow. The operational effectiveness of HLFC aircraft relates to the probability of a partial or complete loss of laminar flow. Four factors were considered: (1) Ice particles in cirrus clouds; (2) Insect contamination; (3) Mechanical failure; and (4) Damage to the suction surfaces. Two computer programs capable of determining the required fuel for a given mission profile have been developed for aircraft in the classes of the B757-200 and the A330-200. The programs were validated against published payload-range data, and modified to emulate the installation of a HLFC system, by incorporating changes to the drag polar, Specific Fuel Consumption (SFC) and Operating Empty Weight (OEW). Sensitivity studies were conducted. The results permit estimates to be determined of the trip fuel reduction of HLFC aircraft compared to equivalent turbulent aircraft. A conceptual design of a HLFC system has been developed for the reference aircraft. A SFC penalty of 1.6% was determined for the B757-200 class aircraft (range: 3272nm, payload: 19147kg) and 2.1% for the A330-200 class aircraft (range: 5980nm, payload: 24035kg) for a system capable of reducing the drag by approximately 14%. The installed system weight represents 2.0% and 1.6% of the OEW for the B757-200 and A330-200 classes of aircraft respectively. The reduction in trip fuel, compared to the turbulent baseline vehicles, was estimated to be 7.4% for these conditions. To obtain the greatest benefit for a HLFC aircraft, the fuel planning must consider the probable time-in-cloud that will result in a loss of laminar flow. An optimised fuel planning approach, which requires a forecast of en route cirrus cloud, has been estimated to further reduce the trip fuel for long-range missions by 2.5 - 3.8%.